2016
DOI: 10.1038/ncomms11212
|View full text |Cite
|
Sign up to set email alerts
|

Serial interactome capture of the human cell nucleus

Abstract: Novel RNA-guided cellular functions are paralleled by an increasing number of RNA-binding proteins (RBPs). Here we present ‘serial RNA interactome capture' (serIC), a multiple purification procedure of ultraviolet-crosslinked poly(A)–RNA–protein complexes that enables global RBP detection with high specificity. We apply serIC to the nuclei of proliferating K562 cells to obtain the first human nuclear RNA interactome. The domain composition of the 382 identified nuclear RBPs markedly differs from previous IC ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(161 citation statements)
references
References 65 publications
2
153
0
Order By: Relevance
“…In addition, comparison of the 344 RICK-exclusive RBPs with three reported human oligo(dT) capture studies 2,18,19 showed that most of these proteins (295, 85.8%) are truly unique to RICK (Fig. 3b and Supplementary Table 3), so we termed them ‘RICK-unique RBPs’.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, comparison of the 344 RICK-exclusive RBPs with three reported human oligo(dT) capture studies 2,18,19 showed that most of these proteins (295, 85.8%) are truly unique to RICK (Fig. 3b and Supplementary Table 3), so we termed them ‘RICK-unique RBPs’.…”
Section: Resultsmentioning
confidence: 99%
“…( a ) Hierarchical clustering of the ion intensities of three different LC-MS/MS experiments ( n = 3 biologically independent experiments for both RICK and oligo(dT) capture (with or without EU)), colors in the heatmap indicate the pairwise Pearson correlation between the different data sets ( n = 1,169). ( b ) Venn diagram comparing the 344 RICK-exclusive RBPs and different oligo(dT) capture studies using human cells 2,18,19 . The serial RNA interactome capture (serIC) study by Conrad et al 19 is a human RNA interactome using oligo(dT) capture of the nuclei of K562 cells.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The catalog of RBPs is diverse, and has grown to include metabolic enzymes, cell cycle regulators, and many other factors not previously associated with RNA biology (Beckmann et al, 2015; Conrad et al, 2016). As this diverse RBP catalog grows, complex regulatory networks are emerging that rely on highly coordinated and concurrent target association by numerous RBPs.…”
Section: Introductionmentioning
confidence: 99%